A NUTRITIONAL APPROACH: EVALUATING VIRGIN COCONUT OIL’S ROLE IN REDUCING LIPID PROFILE AND CRP IN ACS - Abidin, Dr. Sharifah Aisyah Zainal; Mohamed, Prof. Dr. Nurul Azmawati; Aziz , Dr. Muhammad Farid (Global Journal of Medical and Health Science, 2024)
Acute Coronary Syndrome (ACS) presents a burgeoning health concern, marked by an alarming rise in its incidence annually. Statistics underscore its prominence, with the Ministry of Health Malaysia (2017) highlighting cardiovascular diseases as the leading cause of death since the early 1980s. In 2017, non-communicable diseases accounted for a staggering 73% of deaths in Malaysia, with cardiovascular disease standing out as a significant contributor (Ministry of Health Malaysia, 2017a,b). Recognized globally as a critical health issue by the World Health Organization (WHO), ACS demands meticulous strategies for effective management and treatment. In the Malaysian context, statins emerge as a pivotal pharmacological intervention for lowering lipid levels and preventing ACS. Statins, a class of prescription drugs, are specifically designed to mitigate cholesterol levels (Newman et al, 2019). However, their use is not without consequences, as evidenced by statin-related side effects, primarily manifesting as muscle-related issues such as pain, lethargy, weakness, and myopathy (Deichmann et al, 2010; QuMin et al, 2018). This abstract aims to shed light on the pressing issue of ACS, emphasizing its increasing prevalence and the pivotal role of statins in preventive medication within the Malaysian healthcare landscape. By critically examining the statistics and healthcare landscape provided by the Ministry of Health Malaysia, we underscore the urgency of developing effective strategies for ACS management. Furthermore, we delve into the pharmacological aspect, exploring the use of statins as a primary intervention for lipid level control. However, the abstract also acknowledges the associated challenges, particularly the notable side effects of statins reported in observational studies. Muscle-related problems, affecting 10% to 30% of patients in these studies, become a focal point for discussion, necessitating a balanced approach in ACS prevention and treatment .